A phase I study of panobinostat (LBH589) in patients with primary myelofibrosis (PMF) and post‐polycythaemia vera/essential thrombocythaemia myelofibrosis (post‐PV/ET MF). (21st January 2013) - Mascarenhas, John; Lu, Min; Li, Timmy; Petersen, Bruce; Hochman, Tsivia; Najfeld, Vesna; Goldberg, Judith D.; Hoffman, Ronald
Summary Panobinostat (LBH589), a novel histone deacetylase inhibitor (HDACi), was evaluated in a phase I study of patients with primary myelofibrosis (PMF) and post‐essential thrombocythaemia/polycythaemia vera‐related myelofibrosis (Post‐ET/PV MF). Eighteen patients (PMF 56%; Post‐PV MF 28%; Post‐ET MF 17%) were treated in three cohorts at oral doses of (i) 20, (ii) 30, and (iii) 25 mg three times weekly consecutively. Reversible thrombocytopenia was the dose‐limiting toxicity. Five patients (two in Dose Cohort 1, one in Dose Cohort 2 and two in Dose Cohort 3) received six or more cycles and were evaluable for response assessment. After the sixth cycle, three of these five patients achieved clinical improvement (CI) with 100% reduction in palpable splenomegaly from baseline, and two patients experienced stable disease. Panobinostat therapy was also associated with improvement in the degree of anaemia in two of the five patients. Of the three patients who achieved CI after six cycles, one patient achieved a near complete remission after 15 cycles of treatment and another patient had resolution of marrow fibrosis after 16 cycles. We conclude that panobinostat is a well‐tolerated, clinically active treatment for MF patients, regardless of JAK2 V617F status, and most effective when given at low doses over long periods of time.